THE EFFECT OF TRAINING AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE AMONG EMPLOYEES OF RADIO REPUBLIK INDONESIA YOGYAKARTA - Ria Garnita; Ignatius Soni Kurniawan; Nala Tri Kusuma (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The phenomenon at Radio Republik Indonesia (RRI) Yogyakarta reflects the challenges in achieving optimal employee performance due to low participation, limited initiative, ineffective training results, unstructured career development, and weak organizational commitment. This study aims to analyze the effect of training and career development on employee performance with organizational commitment as a mediating variable among employees of RRI Yogyakarta. A quantitative survey approach was used, involving 45 respondents selected through a census method. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) to test the validity, reliability, model-fit, and significance of the relationships between variables. The findings show that both training and career development have a positive and significant effect on employee performance and organizational commitment. However, organizational commitment does not have a direct or significant mediating effect on performance, nor does it significantly influence employee performance. This study highlights the importance of implementing relevant and structured human resource development programs to improve individual competence and organizational productivity. These results provide practical insights for management to strengthen the effectiveness of training and establish clear career paths to support continuous performance improvement.